Palmyrah Palm (Borassus flabellifer L.) Diversity in North Konkan Coastal Region of Maharashtra - MALSHE, K.V.; KHANDEKAR, R. G.; GAWANKAR, M. S. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Palmyrah (Borassus flabellifer L.) is still underutilized important palm in the north Konkan region of Maharashtra. Out of total area in Maharashtra, around 90 per cent area is in only Thane district. Each part of this palm is commercially exploited. It is dioecious palm and there is wide diversity. The survey was carried out during the years 2008 to 2010 in Thane district of Maharashtra state to study the diversity of palms with special reference to sex determination and to collect the elite types of palmyrah having peculiar characteristics. From the surveyed palms the male : female ratio was 1 : 1.46. The palms having peculiar characteristics like high potential of Toddy tapping, nut and kernels quality, growth performance were also identified and selected for further evaluation.